2014
DOI: 10.1371/journal.pone.0087938
|View full text |Cite|
|
Sign up to set email alerts
|

Microrna 130b Suppresses Migration and Invasion of Colorectal Cancer Cells through Downregulation of Integrin β1

Abstract: MicroRNA 130b (miR-130b) is significantly dysregulated in various human tumor types. In this study, using a microarray assay, we characterized the upregulation of miR-130b expression in colorectal cancer (CRC) specimens. However, there is limited knowledge about the roles of aberrant miR-130b expression in CRC. Our studies in CRC cells demonstrated that miR-130b significantly decreases cell migration and invasion, but it has no evidently effects on cell proliferation and apoptosis. In the overexpression miR-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In another study, reactive oxygen species were shown to markedly upregulate the expression of ITGB3, promoting a more aggressive phenotype in a colorectal cancer cell line with increased migratory and invasive capacities [47]. MiRNAs have been linked with the dysregulation of integrin signaling in a number of studies, correlating miRNA-regulated integrin signaling with tumor metastasis and apoptosis in CRC [28], as well as breast, hepatocellular and salivary adenoid cystic carcinoma [7,48,49]. Our findings provide further evidence of the targeting of integrins by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, reactive oxygen species were shown to markedly upregulate the expression of ITGB3, promoting a more aggressive phenotype in a colorectal cancer cell line with increased migratory and invasive capacities [47]. MiRNAs have been linked with the dysregulation of integrin signaling in a number of studies, correlating miRNA-regulated integrin signaling with tumor metastasis and apoptosis in CRC [28], as well as breast, hepatocellular and salivary adenoid cystic carcinoma [7,48,49]. Our findings provide further evidence of the targeting of integrins by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miRNA-30a can act as a tumor suppressor, inducing growth inhibition and suppression of cell migration and invasion in CRC, by targeting denticleless protein homolog, PIK3CD and insulin receptor substrate 2 [25][26][27]. miRNAs have also been reported to modulate the expression of integrins, transmembrane receptors involved in signal transduction, and dysfunction in miRNA-regulated integrin signaling has been linked to tumor metastasis and apoptosis in a number of cancers including CRC [28].…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies of these miRNAs would be helpful for a better understanding of their contribution to the pathophysiology of schizophrenia. The validated downstream target genes for miR-130b include PDGFRA, RUNX3, ITGB1, PPARG, FMR1, and STAT3, and for miR-193a-3p they include ErbB4, S6K2, and MCL1 (33)(34)(35)(36)(37)(38)(39). These genes can be classified into three groups: schizophrenia susceptibility genes (PDGFRA, PPARG, ErbB4), neurodevelopment-related genes (RUNX3, ITGB1, FMR1, STAT3), and neuroprotective genes (S6K2 and MCL1).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Zhao et al [25] demonstrated that ectopic expression of miR-130b suppresses cell proliferation and invasion through inhibition of STAT3 in pancreatic cancer. Another group [26] reported that miR-130b reduces cell migration and invasion through inhibition of integrin β1 in colorectal cancer. The collective evidence implies a tumor suppressor role of miR-130 in metastasis.…”
Section: Discussionmentioning
confidence: 99%